2016
DOI: 10.1007/s11695-016-2247-4
|View full text |Cite
|
Sign up to set email alerts
|

TSH Normalization in Bariatric Surgery Patients After the Switch from l-Thyroxine in Tablet to an Oral Liquid Formulation

Abstract: These results first show that liquid L-T4 could prevent the problem of malabsorption in patients with BPD and confirm those of previous studies in patients submitted to RYGB, suggesting that the L-T4 oral liquid formulation could circumvent malabsorption after bariatric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
54
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 33 publications
7
54
0
2
Order By: Relevance
“…Centanni et al have in fact demonstrated that patients with impaired acid secretion require an increased dose of thyroxine, confirming that normal acid gastric secretion is necessary for the effective absorption of oral L-T4 [25]. Many recent reports have clearly demonstrated that liquid L-T4 formulation circumvents this problem in patients taking proton pump inhibitors, those suffering from gastric-related T4 malabsorption, those ingesting T4 with coffee or fed by enteral tube, and also those submitted to bariatric surgery [2632]. Recently, Giusti et al showed that, in patients affected by DTC, the risk of inadequate TSH levels seems to be more reduced in patients on liquid L-T4 than in those on tablets [17].…”
Section: Discussionmentioning
confidence: 97%
“…Centanni et al have in fact demonstrated that patients with impaired acid secretion require an increased dose of thyroxine, confirming that normal acid gastric secretion is necessary for the effective absorption of oral L-T4 [25]. Many recent reports have clearly demonstrated that liquid L-T4 formulation circumvents this problem in patients taking proton pump inhibitors, those suffering from gastric-related T4 malabsorption, those ingesting T4 with coffee or fed by enteral tube, and also those submitted to bariatric surgery [2632]. Recently, Giusti et al showed that, in patients affected by DTC, the risk of inadequate TSH levels seems to be more reduced in patients on liquid L-T4 than in those on tablets [17].…”
Section: Discussionmentioning
confidence: 97%
“…The liquid formulation has been shown to overcome: 1) the food and beverages interference with L‐T4 tablets absorption, caused by food at breakfast; 2) malabsorption induced by the increased gastric pH, resulting from atrophic gastritis, or due to proton‐pump inhibitors; 3) malabsorption after bariatric surgery; and 4) malabsorption induced by lactose intolerance, or drug interference …”
Section: Introductionmentioning
confidence: 99%
“…Roux-en-Y gastric bypass (RYGB) surgery, a commonly performed operation, can bring about long-term weight loss and excellent remission of associated comorbidities and metabolic disorders [7, 8]. Inconsistent thyroid hormone level alterations in patients with obesity after bariatric surgery were observed in several studies mainly due to different study populations, sample sizes, and surgical procedures [9, 10], emphasizing the need for further research.…”
Section: Introductionmentioning
confidence: 99%